(3Nda NWhW GdPGcQIs (3SjQI PGJjI dLjd GdGeGd GdeDLdIs - (3efJUQ, NGdOs; (3aJMj, JGeQs; (3eMeO, YHO GdQMef fGUQs ((3GdbGgQIs (3QjTI ddfTQ hGdJhRjYs, 2024)
(3SjQI PGJjI djSJ Yf TNU, dcfgG Yf Ref hLjd, Ref aQe LjkdG, hLjd NPdg Ref, Ljd hdO aj VHGH, hSjQMd aj SQGH, Ljd YGT CcKQ ef KhQI, dcfg MJi dMXI hOGYg Yf Jdc GdOfjG de jPbgG, hde jMOO eYfGgG HYO, MVQ HPhQ GdjSGQ, hMVQ CjkVG LeY GdGNhGf ddKeGQ(B. (3HWd QhGjJfG, djS HWkdG, dcfg eLQO eJSGFd, Ydi GdOhGe eJge HMjGRI Ybd, eOGf HLQjeI JaLjQ SDGd, dLC Edi ChQGbg cj jdede ajgG SPGLJg hTWMGJg hhKGFb GJgGeGJg, hba Nda NWhW GdPGcQI hCWdb GdQUGU, jJefi Cf jchf eG GUWGOg ef GdCMQGT bGHkdG ddgVe, hCdG jchf JGQjN UdGMjJg efJgkjGs
Keywords: (3NGdO efJUQs -- (3JQGLes; (3GdCOHGAs; (3GdEYdGes -- (3eUQs